Implementation of Learners' Methods of Memorizing the Qur’an at the Dar El-Iman Indonesia Modern Islamic Boarding School - Aldi Rahmad; Rhadiatul Rahmi; Delvi Salwa Nakita; Zulhiqlal Akbar; Riajasma Putri; Ikhwan Rahman (International Journal of Multidisciplinary Research of Higher Education, 2021)
This study aims to see how the Qur’an memorization program is carried out at Dar El Iman Padang's Integrated Islamic Junior High School. The method used in this research is qualitative with this type of observational research with research data sources obtained from interviews conducted directly with informants who have links with the institutions studied. All interview and observation data were then analyzed thematically using NVivo 12 Software. Based on the results of interviews with informants, it was clear that there were two programs for memorizing the Qur’an at Dar El Iman Padang Islamic Junior High School. The two programs namely; First, tahsin Qur’an for 1 semester, Second, tahfidz Quran 5 juz activities for the next semester. The method applied is the Talaqqi method (direct deposit to the ustadz) in the form of Halaqah half the number of students. With this research, it is hoped that it will become a reference for information for the general public to find out how the Qur’an memorization program is held at the Dar El-Iman Padang Islamic Integrated Junior High School.